Skrining Aktinomisetes Xilanolitik dan Optimasi Produksi Menggunakan Media Tongkol Jagung (Zea Mays L.) Melalui Fermentasi Kultur Terendam - Amelia Fahreza Putri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Actinomycetes are a group of Gram-positive bacteria that are able to form branched unicellular filaments, almost similar to molds. Xylanolytic actinomycetes are actinomycetes that can produce the enzyme xylanase. The production of xylanase requires xylan as a production media, one of which is corn cob with a xylan content of 38%. The production of xylanase with corn cob xylan substrate is carried out through submerged culture fermentation. This study aims to obtain xylanolytic actinomycetes isolates from the tobacco rhizosphere with microscopic and macroscopic morphological characteristics from the three best xylanolytic actinomycete isolates. This research was carried out in several stages, namely the rejuvenation of 40 actinomycetes isolates on ISP-4 media, screening of xylanolytic actinomycetes, hemolysis test, inocular preparation, extraction of xylan from corn cobs, production of xylanase at some incubation time, and partial observation of microscopic and macroscopic morphological characters. The results showed that out of 40 actinomycetes isolates, as many as 39 isolates had xylanolytic ability. The ATG 70, ATG 34, and ATG 36 actinomycete isolates had better enzyme activity index than the other 36 isolates. The production of xylanase by actinomycete isolate ATG 70 was optimal on day 5 with enzyme activity of 7.93 U/mL; ATG 34 on day 4 with enzyme activity of 4.21 U/mL; and ATG 36 on day 5 with an enzyme activity of 6.29 U/mL. Based on microscopic characteristics, the three actinomycetes isolates have spiral chains, so they belong to the genus Streptomyces.
Entry oleh Arif 2026 Januari 29
Keywords: actinomycetes; xylanase; corn cobs